Photo-curable poly-(ethylene glycol) fumarate elastomers with controlled structural composition and their evaluation as eluting systems - Navarro, Lucila (2019)
Elastomeric poly-ester materials have extraordinary potential for soft tissue engineering applications. In connection, in the last 10 years, cross-linkable oligo-(polyethylene glycol fumarate)s emerged as promising materials for obtaining hydrogels for bone tissue engineering applications. In this work weprepared a new family of photo-curable poly-(ethylene glycol)?fumarate elastomers with controlled structural composition. These novel elastomers were obtained by photo-curing of fumarate prepolymers based on diethylene glycol and oligo-ethylene glycols (PEGs 200 and 400), under extremely mild experimental conditions using a low power UV source. The synthesis of fumarate pre-polymers, which were obtained by thermal poly-condensation, and the photo-curing process, were both here discussed on the basis of their structural differences and proposed operating mechanisms. Finally, the photo-radical cross-linking reactions were performed in the presence of anti-cancer drugs (doxorubicin and paclitaxel), in order to evaluate the potential application of the elastomers as new eluting systems.Thus, different release profiles were obtained for hydrophilic (doxorubicin) and hydrophobic (paclitaxel) anticancer drugs, and these differences are discussed on the basis of the structure of the elastomers.